Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1038/eye.2013.172
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of pars plana vitrectomy without internal limiting membrane peeling for optic disc pit maculopathy

Abstract: Purpose To evaluate the results of surgical treatment of maculopathy secondary to congenital optic pit anomaly with pars plana vitrectomy (PPV), endolaser to the temporal edge of the optic disc and C3F8 tamponade without internal limiting membrane (ILM) peeling. Patients and methods Thirteen eyes of 12 patients with serous macular detachment and/or macular retinoschisis secondary to congenital optic disc pit (ODP) were included in the study. All eyes underwent PPV, posterior hyaloid removal, endolaser photocoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 47 publications
4
49
0
Order By: Relevance
“…Also, of the patients with attached macula, 80% required more than 180 days for reattachment to occur. This is in keeping with previous studies that showed that improvement of vision is related to restoration of the normal retinal morphology [10-14, 19, 21, 22, 25-31]. This becomes progressively more evident 6–12 months postoperatively, as submacular fluid is slow to resolve (Table 3).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Also, of the patients with attached macula, 80% required more than 180 days for reattachment to occur. This is in keeping with previous studies that showed that improvement of vision is related to restoration of the normal retinal morphology [10-14, 19, 21, 22, 25-31]. This becomes progressively more evident 6–12 months postoperatively, as submacular fluid is slow to resolve (Table 3).…”
Section: Discussionsupporting
confidence: 76%
“…However, this method of treatment has largely fallen out of favour because the location of laser treatment over the maculopapular bundle can cause significant visual field defects [10, 11, 13]. Our results suggest that laser treatment does not aid in anatomical success.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…2012; Avci et al. 2013), as does the reported spontaneous healing of macular detachment after posterior vitreous detachment (Bonnet 1991). …”
Section: Discussionmentioning
confidence: 75%